Understanding on Leadership of Community Empowerment and Village of Good Governance of The Village Business - Masiyah Kholmi; Diding Suhardi; Ahmad Waluya Jati (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to understanding the good governance based on perspective of Head of Community and Village Empowerment Agency (DPMD). Informants in this research are the Head of Division, Section Head, and community economic business development staff who can represent the research unit in the understanding of good governance in DPMD Jombang Regency. The study was conducted with in-depth interviews with the help of a questionnaire. Data analysis using descriptive qualitative. The results of this study indicate that the Village-Owned Enterprises (BUMDes) are professionally managed, the BUMDes management has the capacity, is able to compile a master plan, understand business, governance refers to guidelines for establishing BUMDes based on Permendes and has Standard Operating Procedures (SOP). BUMDes is managed separately from the village government and there is not much interference from the village government, without being influenced by the pressures of other parties' policies, and can carry out their duties proportionally and can be accounted for. The principles of BUMDES governance include transparency, accountability, responsibility, independence, participation, effective and efficient, and sustainable.